Bibliometric Analysis: Research Trends on Deliberative Models in Learning Approaches in the Digital Era - Muhkam, Mirwan Fikri; Rahmat; Abdulkarim, Aim; Komalasari, Kokom (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to examine the development and trends of research related to deliberative models in learning approaches in the digital era. Research data were obtained using the Publish or Perish 8 application by taking references from journals indexed by Google Scholar. A total of 1000 articles relevant to the keywords